PERBEDAAN HASIL BELAJAR EKONOMI SISWA DENGAN MENGGUNAKAN STRATEGI INFORMATION SEARCH DAN PEMBELAJARAN KONVENSIONAL PADA SISWA KELAS VIII SMP N 10 PADANG - Ananda, Yulia; Armiati, M.Pd, Armiati, M.Pd; Hia, S.Pd, MM, Yulna Dewita (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research was motivated by the low economic learning outcomes eighth grade students of SMP N 10 Champaign Academic Year 2013/2014 . This is caused by the lack of activity of students in the learning process . This study aims to determine the differences in learning outcomes economics students use active learning strategies information search with conventional learning method in class VIII SMP N 10 Padang .This research is an experimental study .Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  The study population was eighth grade students of SMP N 10 Champaign Academic Year 2013/2014 . Samples were taken by purposive sampling technique , VIIIB class was selected as the experimental class and the control class as a class VIIIE . The instrument used was a test of student learning outcomes . Data analysis techniques to test the hypothesis is test â zBased on the analysis of data obtained by the average value of the experimental class 72.8 and class average of 63.00 controls . From the analysis of the data found zhitung value = 2.9156 is greater than the value ztabel = 1.960 at significance level Î± = 0.05, which means that H0 is rejected and Ha accepted .Â Â Â Â Â Â Â Â Â Â Â Â  Â This suggests that there are significant differences between students learning outcomes using active learning strategies information search with conventional learning methods . That is economics student learning outcomes using active learning strategies information search better than economics student learning outcomes learning process using conventional teaching methods in class VIII SMP N 10 PadangÂ